Short-term market reaction vs. Long-term performance: a comparative study of cross-border and domestic M & A by Chinese firms - Ye,Shijing; Zhang,Jiayi (2025)
In this paper, we examine 1437 merger and acquisition (M&A) events that took place between 2015 and 2019 in China, comparing the short-term stock return performance of domestic and cross-border M&A. After that, we further compare the long-term market performance of domestic versus cross-border M&A transactions and investigate the impact of firm-specific and market-related factors on one-year post-merger performance. In the short-term analysis, we adopt the event study methodology and conduct robustness checks using different event windows. For the long-term analysis, we employ the Carhart four-factor model, with robustness tests based on the traditional Fama-French three-factor model. The results show that, there is an initial difference in average cumulative abnormal returns (CAR) between domestic and cross-border M&A, but no significant difference is found in the short-term performance of these two types of M&A events after controlling for firm characteristics. In the long term, both domestic and cross-border M&A transactions exhibit small but positive abnormal returns over the one-year post-announcement period, while domestic M&As tend to yield higher long-term returns. Overall, in the short run, investors do not make a strong distinction between the geographical attributes of M&A in the early stages of an event, and both domestic and foreign M&A events receive a certain amount of market attention and positive response. However, over time, domestic M&As are more likely to realize their strategic value due to factors such as cultural consistency, higher market familiarity, and a more friendly policy environment, thus reflecting better market performance in the long term.
Keywords: M&A performance; Domestic M&A; Cross-border M&A